Syntheses of bismuth titanate templates obtained by the molten salt method - Ranieri, M. G A [UNESP]; Aguiar, E. C. [UNESP]; Cilense, M. [UNESP]; Simões, A. Z. [UNESP]; Varela, José Arana [UNESP] (Elsevier, 2013)
Bismuth titanate templates (Bi4Ti3O12) were synthesized by the molten salt method in Na2SO4 and K2SO4 fluxes, using an amorphous Bi4Ti 3O12 precursor and a mechanically mixed Bi 2O3+TiO2 mixture as the starting materials. The templates were characterized by means of X-Ray Diffraction, FT-IR, FT-Raman, FEG-SEM and TEM. The templates are free of secondary phases and present orthorhombic structure with orientation in the c-plane. FT-IR suggests no traces of sulfate groups revealing that the molten salt synthesis was beneficial for elimination of inorganic species and for the arrangement of individual nanocrystals into ordered lattices. FEG-SEM analyses of BIT templates revealed that most of the grains were homogeneous with a length of 3.1 μm and a width of 0.3 μm and had plate-like morphology. TEM investigations show that the c-axis of the perovskite units is parallel to the thickness direction of the grains and no liquid-phase was formed during BIT phase formation. © 2013 Elsevier Ltd and Techna Group S.r.l.
Keywords: A. Ceramics; B. Chemical syntheses; B. Powder metallurgy; C. X-ray diffraction; Bismuth titanate; Inorganic species; Molten salt method; Molten salt synthesis; Orthorhombic structures; Plate-like morphology; Thickness direction; Amorphous materials; Bismuth; Fluxes; Powder metallurgy; Titanium compounds; X ray diffraction; Fused salts